Assessing the learning curve for transumbilical single-site laparoscopy for endometrial cancer - Li, Fanlin; Zheng, Ying; Yang, Fan; Liu, Jianhong (Frontiers in Oncology, 2024)
Introduction: Applying transumbilical laparoendoscopic single-site surgery in endometrial cancers is worldwide, the depiction of learning curve is rarely described which leads to the vagueness of young clinical practitioners. We accumulated the data to identify the completion of learning curve by analyzing the operative and postoperative outcomes of the patients in endometrial cancer for transumbilical laparoendoscopic single-site surgery (TU-LESS). Methods: This was a retrospective consecutive single-center study of patients with endometrial cancer undergoing standard endometrial cancer comprehensive staging surgery (extrafascial hysterectomy, bilateral salpingectomy and pelvic lymphadenectomy) through TU-LESS by an experienced surgeon from